Development of Students’ Technology, Cognitive and Content Knowledge (TSCCK) through a cloud to enhance Vocational students’ cognitive load and learning achievement - Qiong Wu; Thanin Ratanaolarn (My University, 2023)
Science and technology's applications in education are receiving increasing attention year by year. Based on cognitive load theory, this study used the cloud to develop the TSCCK model for vocational students to improve their cognitive load and academic performance. To define the three cognitive concepts of student technology knowledge (STK), student content knowledge (SK), and student cognitive knowledge (SCK). The study used the research and development method, the steps were: to study, analyze, and synthesize cognitive load theory for the development of the TSCCK model: document research, which includes the data source, research instruments, and data analysis. Finally, through the above three steps, we obtained the following results: Assumption and inspiration about the concept of the model; The original TSCCK model; Cloud with TSCCK.
Keywords: Online Learning and Analytics; Visual and Cognitive Learning Processes; Learning Styles and Cognitive Differences